The occurrence of bisexual strobiles on black spruce ( Picea mariana (Mill.) B.S.P.) in the forest–tundra ecotone: Keewatin, Northwest Territories - Elliott, Deborah L. (Canadian Journal of Forest Research, 1979)
During fieldwork in the summer of 1977 in the vicinity of Ennadai Lake (District of Keewatin, N.W.T., Canada), a stand of upland black spruce (Piceamariana (Mill.) B.S.P.) possessing bisexual strobiles was encountered within the forest–tundra ecotone. This is the first reported occurrence of bisexual strobiles for this species. It is hypothesized that the occurrence of male and female reproductive tissue in the same reproductive structure is an indicator of stress in this arboreally marginal environment.